Construction, characterization and crystal structure of a fluorescent single-chain Fv chimera. (15th February 2021) - Velappan, Nileena; Close, Devin; Hung, Li-Wei; Naranjo, Leslie; Hemez, Colin; DeVore, Natasha; McCullough, Donna K; Lillo, Antonietta M; Waldo, Geoffrey S; Bradbury, Andrew R M
Abstract: In vitro display technologies based on phage and yeast have a successful history of selecting single-chain variable fragment (scFv) antibodies against various targets. However, single-chain antibodies are often unstable and poorly expressed in Escherichia coli . Here, we explore the feasibility of converting scFv antibodies to an intrinsically fluorescent format by inserting the monomeric, stable fluorescent protein named thermal green, between the light- and heavy-chain variable regions. Our results show that the scTGP format maintains the affinity and specificity of the antibodies, improves expression levels, allows one-step fluorescent assay for detection of binding and is a suitable reagent for epitope binning. We also report the crystal structure of an scTGP construct that recognizes phosphorylated tyrosine on FcεR1 receptor of the allergy pathway.